Revolusi Digital dalam Manajemen Sumber Daya Manusia: Implikasi dan Tantangan di Era Teknologi - Fahrel Alfais. A; Jhon Veri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This paper discusses the impact of the digital revolution on human resource management (HRM) in various organizations, focusing on technological advancements such as artificial intelligence (AI), big data, and digital platforms that have significantly transformed HRM practices. The aim of this study is to identify the positive implications and challenges faced by organizations in adopting digital technologies. The method used is a systematic literature review from various academic and practical sources, which provides in-depth insights into current trends and practices in HRM. The research findings indicate that while digital technology improves efficiency and productivity, challenges such as resistance to change and the need for new skills remain. Organizations often struggle to integrate new technologies into existing work cultures and ensure that employees possess the necessary skills to effectively leverage these technologies. Therefore, this paper offers recommendations for adaptation strategies that organizations can implement, including the development of ongoing training programs, fostering an innovation-driven culture, and updating privacy and data security policies. By understanding and addressing these challenges, organizations can harness the full potential of the digital revolution to enhance their performance and competitiveness.